Congestion and Residential Moving Behaviour in the presence of Moving Costs - Ninette Pilegaard; Morten Marott Larsen; Jos Van Ommeren (European Regional Science Association (ERSA), 2005)
In this paper we study how congestion and residential moving behaviour are interrelated using a two-region job search model. We demonstrate that depending on the amount of commuting and residential moving between regions, a congestion tax may lead to both welfare losses and gains. In the analysis of optimal location of households it is often assumed that households may move residence at no costs. The model developed in this paper allows for incomplete information in the labour market combined with residential moving behaviour and positive residential moving costs. We examine welfare consequences of both homogenous and heterogeneous moving costs. Workers choose optimally between interregional commuting and residential moving to live closer to the place of work. This choice affects the external costs of commuting due to congestion. Therefore, road pricing (or congestion taxes) may not only reduce congestion but also increase total residential moving costs in the economy. One of the main consequences is that the road tax does not necessarily increase welfare. In some cases, the assumption of moving costs (homogenous or heterogeneous) has implications for the interpretation of the results.
Keywords: 330